Non-compliance of Hospital X Employee in Implementing Standard Operational Procedures of Instrument Decontamination and Chest X-Ray Services - Prahadiani, Saesar Revita; Kuncoro, Wahyudi; Hariyanti, Tita; Zuhriyah, Lilik; Sarwiyata, Tri Wahyu; Pradina, Fifin (Jurnal Kedokteran Brawijaya, 2024)
Good hospital management is important to maintain the safety of patients, staff and hospital visitors. Each hospital employee responsible for patient safety by carrying out work according Standard Operating Procedure (SOP) guidelines agreed by organization. This study aims to identify the casues factors and the solution for hospital employees to not comply with the SOP. This study uses a qualitative descriptive approach. Methods of data collection by conducting direct observation and interviews. Subjects in the study were determined based on purposive sampling, as many as 8 respondents consisting of the inpatient room's head, nurses and radiology officers. It is important to apply a system approach in the management of an organization. The elements included in the systems approach are planning, organizing, actuating and controlling. From those elements, there are things that not properly carried in the hospital. The existing procedures were not followed by the employees, for example, procedures regarding instrument decontamination in the inpatient room and photo reading at the radiology service. Non-compliance with this procedure is influenced by several factors, namely the staff lack of discipline and responsibility, inappropriate procedures, facilities that are not available, and there is no socialization of the procedure to hospital employees. The non-compliance of employees at X hospital was caused by procedural factors, decontamination and radiology officer's performance factors and hospital's facilities. For this reason, it is necessary to conduct periodic outreach, monitoring and evaluation of the SOP and hospital employees to improve the quality of hospital services and customer satisfaction.